Stabilitas Bank Syariah dan Bank Konvensional di Indonesia: Comparative Analylis - fellasufah diniyah (STEI Kanjeng Sepuh Gresik Jawa Timur, 2023)
This research aims to measure the financial stability of Islamic and conventional banks and compare the results of financial stability between the two banks. In this research, financial stability will be measured using the Z-score. This study, it is also to determine the influence of credit risk (NPF/NPL), liquidity risk (FDR/LDR), efficiency ratio (BOPO) on the stability of sharia and conventional banking in Indonesia in the 2015-2019 period. This research uses panel data analysis. Sampling used a purposive sampling technique and 10 Islamic and conventional banks were obtained that met the criteria. The results of this research show that variabel credit risk (NPF), liquidity risk (FDR), efficiency ratio (BOPO) have a significant effect on the stability of Islamic and conventional banks. Partially, credit risk has a negative and significant effect on sharia banking, while on conventional banking it has a positive and significant effect. Liquidity risk in sharia banking has a positive and significant effect, whereas it has no effect in conventional banking. The efficiency ratio has no effect on sharia and conventional banking. Based on test results, conventional banking is more stable than sharia banking.